An Effective and Automated Processing of Resonances in Vibrational Perturbation Theory Applied to Spectroscopy - Yang, Qin; Bloino, Julien (The journal of physical chemistry. A, 2022)
The broader availability of cost-effective methodologies like second-order vibrational perturbational theory (VPT2), also in general-purpose quantum chemical programs, has made the inclusion of anharmonic effects in vibrational calculations easier, paving the way to more accurate simulations. Combined with modern computing hardware, VPT2 can be used on relatively complex molecular systems with dozen of atoms. However, the problem of resonances and their corrections remains a critical pitfall of perturbative methods. Recent works have highlighted the sensitivity of band intensities to even subtle resonance effects, underlying the importance of a correct treatment to predict accurate spectral bandshapes. This aspect is even more critical with chiroptical spectroscopies whose signal is weak. This has motivated the present work in exploring robust methods and criteria to identify resonances not only in energy calculations but also on the transition moments. To study their performance, three molecules of representative sizes ranging from ten to several dozens of atoms were chosen. The impact of resonances, as well as the accuracy achievable once they are properly treated, is illustrated by the changes in spectral bandshapes, including chiroptical spectroscopies.